2012
DOI: 10.2174/1875035401205010008
|View full text |Cite
|
Sign up to set email alerts
|

Understanding How Plasmodium falciparum Binds to the Placenta and Produces Pathology Provides a Rationale for Pregnancy-Associated Malaria Vaccine Development

Abstract: By adulthood repeated exposure to Plasmodium falciparum, the causative agent of the most severe form of malaria in humans, can induce semi-immunity to clinical infection. During pregnancy, however, there is a striking recurrence of severe disease, a syndrome described as pregnancy-associated malaria (PAM). This is caused by P. falciparum-infected erythrocytes binding to receptors on the placental endothelium that are expressed uniquely during pregnancy. This subset of parasites binds by virtue of expressing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 119 publications
(258 reference statements)
0
5
0
Order By: Relevance
“…In regard to pregnancy, the natural build-up of immunity over successive pregnancies due to production of antibodies that recognize placental parasites and which prevent their binding to the placenta suggest the feasibility of developing a pregnancy-associated vaccine [25,75]. Serological studies indicate that a single or finite number of antigens may be required in order to elicit protective immunity based on the production of parasite-specific antibodies [76].…”
Section: Placental Sequestrationmentioning
confidence: 99%
“…In regard to pregnancy, the natural build-up of immunity over successive pregnancies due to production of antibodies that recognize placental parasites and which prevent their binding to the placenta suggest the feasibility of developing a pregnancy-associated vaccine [25,75]. Serological studies indicate that a single or finite number of antigens may be required in order to elicit protective immunity based on the production of parasite-specific antibodies [76].…”
Section: Placental Sequestrationmentioning
confidence: 99%
“…[34] It should also reproduce, or better still, improve upon naturally acquired immunity and be long-term without necessary boosters or interference from other vaccines. [35] Finally, it should be inexpensive to manufacture and purchase. Unfortunately, malaria vaccines are unlikely to fulfil some of this 'wish list' of properties.…”
Section: Identifying the Knowledge Deficitmentioning
confidence: 99%
“…Instead, it is more probable that they will be moderately effective, confer short-term immunity and be difficult and expensive to make. [34][35][36] mAlArIA vAccInes -current stAte Due to the shortfall in effectiveness of other malaria control measures, increased attention on vaccines led to the formation in 1999 of the PATH Malaria Vaccine Initiative (MVI), a non-government organization (NGO) based in Washington DC, USA, which facilitates accelerated testing of malaria vaccines. [37] There are currently around 63 documented malaria vaccine candidates, including 41 in preclinical and clinical trials.…”
Section: Identifying the Knowledge Deficitmentioning
confidence: 99%
“…It has been estimated that about 26% of maternal anemia is due to malaria. In Africa, it was reported that severe anemia as a result of falciparum malaria is responsible for approximately 10,000 maternal deaths per annum [ 2 ]. Infants with congenital malaria also experience devastating effects from the infection.…”
Section: Introductionmentioning
confidence: 99%